Enhancing Security in Affordable Housing: The Case of Prince Fawaz Project - Maged Attia (Alanya Hamdullah Emin Paşa Üniversitesi, 2021)
The present study argues that the urban form of affordable housing projects affects safety and security. The study examines the level of safety and security in the Prince Fawaz project proposing recommendations that enhance it. Theories and approaches concerned with the environmental crime are initially reviewed. Then, urban and architectural features as well as crime rates and patterns are documented. Also, trace and behaviour observations are carried out. The observations monitored urban features and behaviours associated with crime or fear of crime. Residents’ perception for security and fear of crime is extracted through a questionnaire. A Space Syntax is processed and linked with the questionnaire and observation outputs. Observations demonstrate a semblance of fear of crime which is supported by records of car and home theft. Although the questionnaire reflects a suitable level of security, it points to peripheral spaces and areas around mosques and shops as the less secure. However, enhancing security in the Prince Fawaz project requires urban interventions including controlling access to peripheral spaces, reviving areas detected to be unsafe, repositioning elements causing visual obstacles and enhancing appearance by vegetation and sustainable maintenance. Besides, reformulating the movement network so that an appropriate integration between residents and strangers is achieved. On the conceptual level, the study proves that none of the theories of environmental crime can act as a comprehensive approach; but each can partly work.